Development of Arabic Language Learning in Indonesia at 19th – 21st Century - Azizah, Nur Laila; Naifah, Naifah; Afrianingsih, Baiq Intan; Hamidah, Millatul; Audl Ramadlan, Muhammad Athif (Universitas Islam Negeri Raden Intan Lampung, 2024)
Arabic language learning has a long history in Indonesia, starting from the 19th century. This article aimed to provide a comprehensive historical overview of the development of Arabic language learning in Indonesia from the 19th century to the 21st century. A qualitative approach and the historical review method with quasi descriptive research model were applied. This article examined the evolution of teaching methods, curriculum and media used in Arabic language learning. In this research, the primary sources were the official reports, curriculum, textbooks, journals, and historical records, as well as secondary sources such as academic literature and research publications. This article traced the shifts and transformations in Arabic language teaching practices in Indonesia. Through content analysis and historical interpretation, key milestones, trends and factors were identified which shaped the trajectory of Arabic language learning over the past three centuries. The findings revealed diverse influences, ranging from the traditional Islamic education system to modern learning models that keep up with the times. This article highlighted the unique challenges and adaptations that have characterized the development of Arabic language learning in Indonesia. By offering a historical perspective on the evolution of Arabic language learning methods and approaches, this article contributed to a deeper understanding of the current state of Arabic language education in Indonesia. The insights gained from this research could inform the future strategies and policies aimed at improving the quality and effectiveness of Arabic language learning and preserving the nation's cultural and linguistic heritage.